In-service fatigue fracture mechanisms in covered disks of a TV3-117VK helicopter turbine engine - Shanyavskii, A.A.; Potapenko, Yu.A. (Проблемы прочности, 2008)
In-service propagatingfatigue cracks were examined in EI-698VD superalloy thin turbine covered disks ofthefirst, second, and third stages ofa TV3-117VK helicopter engine within service lifes of 200-1800 h. To reveal causes of early crack initiation and estimate a propagation time, metallographic and fractographic analyses were performed. The sequence of events during fatigue cracking o f the disks was established. A block of striations on the fracture surface was discovered, which characterized fatigue crack propagation during one flight of a helicopter under different operating conditions. The number o f striations in each block varied over the range of 4-20, being much more than those used to design covered disks. Fractographic results were used to estimate fatigue crack growth in covered disks of different stages using data on different operating conditions of helicopters.